Dynamic Macroeconomic Models in Emerging Market Economies DSGE Modelling with Financial and Housing Sectors - Jia, Daniel Lukui; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Palgrave Macmillan, 2020)
This book summarizes the evolution of modern macroeconomics (New Consensus Macroeconomics, NCM) and proposes a new approach to theoretical and empirical analysis, which is based on a recently developed dynamic stochastic general equilibrium (DSGE) model. Dynamic macroeconomic analysis in emerging market economies is challenging, and of growing importance in the global economy, where emerging markets are becoming more and more influential. Clearly, a deeper understanding of the inner workings of emerging economies, particularly with respect to their socioeconomic structure and the urbanization process, is needed. The book$1 (Bs extends the NCM/DSGE model to better account for significant economic and social features in emerging market economies. In particular, household heterogeneities and social stratification are explicitly incorporated into the framework proposed here, substantially enhancing the comprehensiveness of the model economy, and allowing it to better account for underlying social structure in emerging economies. Furthermore, financial and housing markets have not been considered sufficiently in either the advanced or emerging economy literature, an oversight this book remedies. As such, it makes an original and valuable contribution to the field, and a direction for future research. Daniel Lukui Jia holds a Ph.D. from Cambridge University. His research interests include macroeconomics, dynamic modeling, money and banking, and public finance.s
Part I Introduction -- Chapter 1 Introduction to Modern Macroeconomic Models -- Chapter 2 Time to Improve the Existing Models -- Part II Dynamic Macroeconomic Modelling -- Chapter 3 Traditional Dynamic Macroeconomic Models -- Chapter 4 Modern Mainstream Macroeconomic Models -- Part III The Financial and Housing Sectors Asymmetric Model for Emerging Market Economies -- Chapter 5 Overview and General Assumptions -- Chapter 6 The Basic Model -- Chapter 7 The Advanced Model -- Chapter 8 The Full Model -- Chapter 9 Solving DSGE models -- Part IV Empirical Analysis -- Chapter 10 Empirical Methodologies and Software Tools -- Chapter 11 Data, Statistics and Stylized Facts -- Chapter 12 Empirical Analysis -- Part V Summary -- Chapter 13 Conclusion and Discussion -- Index.
Keywords: Globalization; Markets; Macroeconomics; Emerging Markets/Globalization.; Macroeconomics/Monetary Economics//Financial Economics